Cooperatives amid the Wave of Industrial Revolution 4.0: Opportunities and Challenges - Siswanto, Irvan; Budiman, Fajar; Aini, Farida; Kurniawan, Fiki; Aulia, mesyha Suswita (Indonesian Journal of Islamic Economics and Finance, 2024)
This study examines the roles and challenges faced by cooperatives in the era of Industry 4.0, focusing on adapting digital technologies to enhance member welfare and economic growth. The research employs a comprehensive literature review, case studies, and content analysis of publications from the past decade. Findings indicate that digitalization has increased operational efficiency in cooperatives by up to 40%, expanded market access, and improved transparency and accountability. However, key challenges include the persistence of the digital divide, high initial investment costs, and the need for cultural change within organizations to support digital transformation. Government support, including digital literacy training and access to financing, is crucial in accelerating this transformation process. The practical implications of this study highlight the necessity for broader digital training programs, access to low-interest financing for technology investments, and the development of adequate digital infrastructure. This research underscores significant progress in technology adoption among cooperatives and the positive socio-economic impacts that result from it. As a result, digital transformation within cooperatives holds substantial potential for fostering more inclusive and sustainable economic growth.